Study of Work Motivation, Work Discipline, and Communication on Employee Organizational Commitment - Juniarti Juniarti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the influence of Work Motivation, Work Discipline, and Communication on Employee Organizational Commitment. This type of research is a descriptive qualitative study using a literature review method based on previous research journals. The results of this study explain that there is a relationship between work motivation, work discipline, and work communication in enhancing organizational commitment. To determine an employee's organizational commitment, one must consider their motivation to work, discipline in adhering to existing regulations, and ability to communicate well to take necessary actions in achieving the company's vision and mission. In this regard, it is necessary to instill a sense of responsibility in all employees, making them aware of their significant role within the organization, involving employees in every activity aimed at achieving organizational goals, and fostering a sense of belonging to the organization. This is intended to cultivate a strong emotional bond between employees and the organization, making it easier to achieve organizational goals if every employee has a strong commitment to the organization.